Reporting Melanoma: A Nationwide Surveillance of State Cancer Registries. (29th December 2015) - Raji, Kehinde O.; Payne, Lauren; Chen, Suephy C.
Abstract : The goal of our study was to determine current melanoma reporting methods available to dermatologists and dermatopathologists and quantify changes in reporting methods from 2012 to 2014. A cross-sectional study design was utilized consisting of website perusal of reporting procedures, followed up by telephone and email inquiry of reporting methods from every state cancer registry. This study was conducted over a six-month period from February to August 2014. A previous similar survey was conducted in 2012 over the same time frame and results were compared. Kansas state cancer registry provided no data. As of August 2014, 96% of 49 state cancer registries had electronic methods available to all designated reporters. Seven (14%) states required an electronic-only method of reporting melanoma cases. Eighty-six percent allowed hard copy pathology report submission. Compared to the 2012 survey, 2 additional states were found to have initiated electronic reporting methods by 2014. In conclusion, a variety of methods exist for reporting diagnosed melanoma cases. Although most state cancer registries were equipped for electronic transmission of cases for mandated reporters, a number of states were ill-equipped for electronic submission from outpatient dermatologists. There was a general trend towards electronic versus nonelectronic reporting from 2012 to 2014.